Italian agricultural policy in the Green Mountain / Libya 1911-1942 AD - Elderaani, Ghaliya Younis; alsheikh, Sageda (Sharwes Scientific Journal, 2025)
God has blessed the Green Mountain area with distinctive geographical and climatic factors, qualifying it – throughout historical eras – as a region for good and diverse agricultural production, in addition to its natural reserves of livestock and natural forests. Herein lies the focus of the study's problem in the main question: What are the components and methods of Italian agricultural policy in the Libyan Green Mountain region? The study aims to identify the natural components for agriculture in the Green Mountain, clarify agricultural methods in the Green Mountain before Italian colonization, and highlight the most important agricultural policies in the Green Mountain during the Italian era. The study followed a historical methodology based on narrating historical events and facts, and an analytical approach to study and analyze the components and methods of Italian agricultural policy in the Libyan Green Mountain region. The study arrived at several results, the most important of which are: the Italians took an interest in agriculture in the Green Mountain and implemented several agricultural programs aimed at settling and developing the area, facing numerous agricultural problems and having various ways to solve those problems, One of the most important agricultural problems faced by the Italians is: resistance from the locals and thus instability, the water problem, the demographic decline of the population, the issue of agricultural pests, and also the problem of primitive agricultural methods.